2013
DOI: 10.1093/icvts/ivt186
|View full text |Cite
|
Sign up to set email alerts
|

B-type natriuretic peptide as a biochemical marker of left ventricular diastolic function: assessment in asymptomatic patients 1 year after valve replacement for aortic stenosis

Abstract: OBJECTIVES: Left ventricular (LV) diastolic dysfunction after aortic valve replacement (AVR) carries a substantial risk of development of heart failure and reduced survival. In addition to echocardiography, B-type natriuretic peptide (BNP) provides a powerful incremental assessment of diastolic function. This study evaluates BNP as a marker of LV diastolic dysfunction in a cohort of patients with preserved LV ejection fraction who underwent AVR for pure aortic stenosis and the relationship between BNP values a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…Thirty studies were cross-sectional [ 18 , 20 , 22 , 32 58 ] and twenty-one [ 31 , 59 78 ] were case-control studies (Tables 1 and 2 ). Twenty-eight were performed in Europe [ 20 , 32 36 , 38 , 40 , 41 , 43 45 , 50 , 52 , 53 , 55 – 57 , 59 , 63 , 64 , 66 , 69 , 73 , 76 78 ], 11 in North America [ 22 , 37 , 39 , 46 , 49 , 54 , 65 , 70 , 72 , 74 , 75 ], 11 in Asia [ 31 , 42 , 47 , 51 , 58 , 60 62 , 67 , 68 , 71 ] and one was a multi-country study [ 48 ]. The control populations were either healthy controls ( N = 14) [ 31 , 35 , 59 , 60 , 62 , 65 , 67 69 , 71 , 72 , 75 – 77 ] or were recruited at the same department as the patient population, but without DD or HFpEF ( ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty studies were cross-sectional [ 18 , 20 , 22 , 32 58 ] and twenty-one [ 31 , 59 78 ] were case-control studies (Tables 1 and 2 ). Twenty-eight were performed in Europe [ 20 , 32 36 , 38 , 40 , 41 , 43 45 , 50 , 52 , 53 , 55 – 57 , 59 , 63 , 64 , 66 , 69 , 73 , 76 78 ], 11 in North America [ 22 , 37 , 39 , 46 , 49 , 54 , 65 , 70 , 72 , 74 , 75 ], 11 in Asia [ 31 , 42 , 47 , 51 , 58 , 60 62 , 67 , 68 , 71 ] and one was a multi-country study [ 48 ]. The control populations were either healthy controls ( N = 14) [ 31 , 35 , 59 , 60 , 62 , 65 , 67 69 , 71 , 72 , 75 – 77 ] or were recruited at the same department as the patient population, but without DD or HFpEF ( ...…”
Section: Resultsmentioning
confidence: 99%
“…Five DD studies included patients with HFpEF [ 38 , 43 , 48 , 73 , 76 ], one DD study included patients with signs and symptoms [ 44 ], but did not exclude on LVEF, and eight DD studies only included patients with LVEF above 45 or 50% [ 18 , 20 , 45 , 47 , 50 , 52 , 53 , 77 ]. The reference diagnoses used in the included studies varied from use of maximal velocity of the E-wave (e’) ( N = 10) [ 43 45 , 49 , 50 , 52 , 54 , 56 , 57 , 74 ] versus no tissue Doppler (TDI) measures ( N = 14) [ 18 , 20 , 22 , 38 , 46 48 , 51 , 53 , 55 , 73 , 76 78 ] for DD studies and, use of extensive criteria ( N = 13) [ 31 , 32 , 34 , 35 , 38 , 41 , 59 , 61 , 63 , 64 , 66 , 69 , 72 ], signs and symptoms of HF in combination with LVEF ( N = 11) [ 36 , 40 , 42 , 58 , 60 , 62 , 65 , 67 , 68 , 70 , 71 ], expert opinion ( N = 1) [ 33 ] or catheterization ( N = 3) [ …”
Section: Resultsmentioning
confidence: 99%
“…Patients with moderate to severe AS usually have concentric LV hypertrophy associated with myocardial dysfunction due to abnormal calcium handling and increased myocardial interstitial fibrosis, which produces early LV diastolic abnormalities, left atrial remodeling , and late systolic chamber dysfunction . Mannacio et al demonstrated that BNP values are directly related to several transmitral flow parameters and tissue Doppler findings, indicative of impaired LV diastolic function in AS patients pre‐ and post‐AVR. In a recent study of 125 AS patients who have not undergone valve surgery, E/E′ ratio was the most predictive parameter of clinical events among clinical and imaging measurements .…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, NT-proBNP was found to be the sole predictor of high preoperative LV filling pressure, after adjusting for confounders. Additionally, previous studies have shown an association between NT-proBNP and diastolic function 37,[147][148][149][150] . Our method for the evaluation of high LV filling pressure, starting with E/A taking the age adjusted normal ranges into account for grading of diastolic function, was at least as good as left atrial index and E/é in identifying patients with increased levels of NT-proBNP.…”
Section: Diastolic Dysfunction Nt-probnp and Phfmentioning
confidence: 93%